Investigating the Integration of Big Data Technologies in Higher Education Settings - Khatera Akrami; Mursal Akrami; Fazila Akrami; Musawer Hakimi (PT Ilmu Data Indonesia, 2024)
The integration of big data technologies in higher education is a topic of growing interest due to its potential to revolutionize teaching, learning, and administrative processes. This study aims to explore the impact of big data technologies on educational practices and outcomes in higher education settings. Through a comprehensive investigation, including literature review, surveys, and statistical analysis, the study examines the utilization, effectiveness, and challenges associated with integrating big data technologies in educational settings. Key findings reveal a significant positive correlation between the utilization of big data technologies and the frequency of interaction among faculty, researchers, and practitioners. Additionally, faculty training is identified as a crucial factor influencing the successful integration of big data technologies in higher education. Institutional support emerges as a key facilitator in the effective implementation of big data technologies, while student readiness, including technological proficiency and willingness to engage, is found to positively correlate with integration efforts. The perceived effectiveness of big data technologies mediates the relationship between integration efforts and outcomes in higher education settings. Based on these findings, recommendations are provided to enhance the integration of big data technologies in higher education, including the need for continuous faculty training, institutional support, and student readiness initiatives. Overall, this study contributes to the ongoing discourse on leveraging data-driven approaches to enhance educational practices and outcomes in higher education.